Gender gaps in labor market participation and earnings in post-reform China / Saizi Xiao - Saizi , Xiao (2020)
Ensuring gender equity in the process of economic development is a key Sustainable Development Goal. Many governments have invested heavily in women’s education to address gender inequality in the labor market. However, gender gaps in labor force participation and earnings continue to persist even in developing countries that have experienced steady macroeconomic growth and graduated to upper middle income status. A case in point is China, the country with the largest labor force in the world, where gender gaps in labor force participation rates and earnings have widened during the transition from a centrally planned economy to a market-oriented one. This phenomenon has received some attention from researchers in post-reform China. However exactly what is driving these gaps in post-reform China is not fully understood. Therefore, this dissertation contributes to the existing literature by re-examining the determinants of labor force participation and earnings as well gender gaps in these two labor market indicators using data from the Chinese General Social Survey (CGSS) 2010. The dissertation contains two parts. In the first part, Probit regression model of participating in the labor force together with Oaxaca decomposition for non-linear model are employed to to investigate the size and sources of the gender labor force participation gap. The empirical analysis additionally takes into account the role of previously ignored factors – social norms, health human capital and cognitive skills – in explaining this gap. In the second part, the analysis is based on the Mincerian earnings function which is estimated using the Ordinary Least Squares method and also complemented with the Oaxaca decomposition analysis. Moreover, Heckman and Instrumental Variables approaches are used for corrections of problems such as non-random selection into the labor force and endogeneity of schooling attainment in the earnings function. First part of the analysis found a significant gender gap in labor force participation probability. Detailed decomposition showed that only a small portion of the gender gap in participating in the labor force was explained by endowment differences such as superior health human capital. Instead, gender-related community social norms accounted for around half of the unexplained gap. In the second part, a significant differential of average monthly earnings between females and males was found. Detailed decomposition indicated that only one third of the gender gap in monthly earnings was explained by endowment gaps such as superior health and education capital. While the majority of this gap remains unexplained by difference in returns to these conventional endowments. Moreover, these findings are robust to corrections for problems including sample selection bias and endogeneity of schooling attainment. The findings have important policy implications. Interventions that can narrow gender gap in pre-market health status through improved access to health facilities and medical services would help to narrow the gender gap in Chinese labor market. In addition, policies that improve access to higher English educational opportunity for women and promote supportive attitudes within the community towards women’s outside work are also likely to help close the gender gap in labor force participation rate.